Ka.Jian Pengembangan Sistem Transportasi Terpadu Di Provinsi Nad - Motholib, Abdul; Mutharuddin, Mutharuddin; Bastaman, Sukhiar (Warta Penelitian Perhubungan, 2010)
Nanggrre Aceh Oamssnlnm (NAO) illl' n luge 11nturnl resources potentinl mid stmtegic position 1wt also fornati011£11links/local but akso inenuztional economic linJcyregi011£11, wich can re ~cted to re the new economic power inantidpatingfree trade policy. Therefore increasing the eamomic capaa:ty should re supported by intergrated tra11SfX11'tationsystem with increasing accessibility of transportation males such as air trcmspartation, sea transportation, andland transportation. The fature transportation trend is focused to intermaial and multimaial StJStem. The main paintof integrated transp:;rt in intennaial nnd nrultinwinl smles is to estnblis/1 trm1Sp0rlntion wich is efective, efficient,faster,safety, dmrx:r nnd realible. Otherwise, the problems ofi11 tegrnted hw isportntion Sl)Stem in NAO are infastructureojhi.ghway, airport, seaport, transpartntion fadlities, mui lm'ui use plmming. Four steps mcxieling is used to mlibrate themcxiel with using transportation network existing, social ecmwmic data, land use 'jXltfern, and justijimtion of generaJ,iz.ed cost in their links and nodes which are influenced bt some variables such as value of time, trcrocl time, logistic fore andlogistic demand. The studt; results that total ccst of sea transportation is 10U£r than total cost ofland transportation. Sothat, infrastudures and facilities in]:rownent to and in Sfil?XYrl are needed to redua waiting time.